2003
DOI: 10.1017/s0012162203001270
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and mental health problems in children with epilepsy and low IQ

Abstract: The purpose of this cross-sectional descriptive study was to describe the particular types of behavioral problems, self-concept, and symptoms of depression experienced by children with both low IQ and epilepsy. Three groups of children (83 males, 81 females; mean age 11 years 10 months, SD 1 year 10 months; age range 9 to 14 years) with epilepsy were compared: (Group 1) Low IQ (<85), n=48, 25 males, 23 females; (Group 2) Middle IQ (85 to 100), n=58, 24 males, 34 females; and (Group 3) High IQ (>100), n=58, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 41 publications
7
45
1
5
Order By: Relevance
“…The ratings by both parents and teachers on these scales are beyond or approaching 1 SD above the normative mean, suggesting that, as a group, the sample was rated as being in or approaching the At-Risk range in each of these areas. This finding is consistent with previous research using the CBCL (e.g., Buelow et al, 2003;Freilinger et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The ratings by both parents and teachers on these scales are beyond or approaching 1 SD above the normative mean, suggesting that, as a group, the sample was rated as being in or approaching the At-Risk range in each of these areas. This finding is consistent with previous research using the CBCL (e.g., Buelow et al, 2003;Freilinger et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Their seclusion leads to their limitation of using public facilities [7]. In this regard, Henley, Ramsey, and Ozzine [8] suggested that behavioral-emotional problems in children would lead to communication problems.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with epilepsy are at high risk for death (21,22) and comorbidities, including cognitive impairment (23) and depression (24)(25)(26). While the comorbidities of epilepsy extend across the life span of an individual, they are not uniform across the age groups.…”
Section: Introductionmentioning
confidence: 99%